Can Neonatal Pneumoperitoneum be Managed by Conservative Management Alone? - Pati, Sananda; Chaki, Bhushan; Roy, Atanu; De, Sangita (Journal of Nepal Paediatric Society, 2013)
Common causes of pneumoperitoneum in neonates includes necrotising enterocolitis (NEC), specific infections, gastro intestinal obstruction, iatrogenic causes, idiopathic focal intestinal perforation, perforation secondary to intra thoracic pathology, mechanical ventilation etc. Primary peritoneal drainage and exploratory laparotomy remain the definitive management of pneumoperitoneum in neonates. Here we report a case of suspected spontaneous idiopathic intestinal perforation managed conservatively with monitoring of vital signs. The neonate had an uneventful recovery. This case highlights the need to identify infants with benign or non surgical causes of pneumoperitoneum thus avoiding unnecessary laparotomies and referrals in these vulnerable neonates. DOI: http://dx.doi.org/10.3126/jnps.v32i3.5912 J. Nepal Paediatr. SocVol.32(3) 2012 252-253